2004
DOI: 10.1103/physreve.70.050902
|View full text |Cite
|
Sign up to set email alerts
|

Granger causality and information flow in multivariate processes

Abstract: The multivariate versus bivariate measures of Granger causality were considered. Granger causality in the application to multivariate physiological time series has the meaning of the information flow between channels. It was shown by means of simulations and by the example of experimental electroencephalogram signals that bivariate estimates of directionality in case of mutually interdependent channels give erroneous results, therefore multivariate measures such as directed transfer function should be used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
178
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(180 citation statements)
references
References 22 publications
1
178
0
1
Order By: Relevance
“…In contrast, EEG studies in healthy controls have revealed a front-to-back pattern of directed connectivity, particularly in the alpha band (17)(18)(19)(20)(21)(22), consistent with modeling studies that have shown that such patterns may arise due to differences in the number of anatomical connections (the degree) of anterior and posterior regions (22,23). However, modeled patterns of information flow depend on the assumed strength of the underlying structural connections (22)(23)(24), and the observed EEG patterns strongly depend on the choice of reference (25), which may explain why, controversially, the reverse back-tofront pattern has also been observed in EEG (26)(27)(28). An important advantage of MEG over EEG in this context is that it is referencefree.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…In contrast, EEG studies in healthy controls have revealed a front-to-back pattern of directed connectivity, particularly in the alpha band (17)(18)(19)(20)(21)(22), consistent with modeling studies that have shown that such patterns may arise due to differences in the number of anatomical connections (the degree) of anterior and posterior regions (22,23). However, modeled patterns of information flow depend on the assumed strength of the underlying structural connections (22)(23)(24), and the observed EEG patterns strongly depend on the choice of reference (25), which may explain why, controversially, the reverse back-tofront pattern has also been observed in EEG (26)(27)(28). An important advantage of MEG over EEG in this context is that it is referencefree.…”
supporting
confidence: 56%
“…17-22, but see refs. [26][27][28] is that the patterns of directionality in EEG strongly depend on the choice of reference (25). MEG, in contrast, is reference-free.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are due to: (i) unrobust methods of connectivity estimation, and, even more important, (ii) application of bivariate methods. The mechanism of generation of false connections in the case of bivariate networks was elucidated in [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Granger causality 2 refers to a family of synchrony measures that are derived from linear stochastic models of time series; as the above linear interdependence measures, they quantify to which extent different signals are linearly interdependent (see (Granger , 1969;Kamiński et al, 1991Kamiński et al, , 2005Gourévitch et al, 2006;Korzeniewska et al, 2003;Eichler, 2006;Blinowska et al, 2004;Ancona et al, 2004;Astolfi et al, 2004Astolfi et al, , 2005Schelter et al, 2005;Chen et al, 2006) for detailed information about Granger causality). Whereas the linear interdependence measures of Section 2.1 to 2.4 are bivariate, i.e., they can only be applied to pairs of signals, Granger causality measures are multivariate, they can be applied to multiple signals simultaneously.…”
Section: Granger Causalitymentioning
confidence: 99%